EVALUATION OF THE PROGRAM OF EDUCATION AND TRAINING FOR PROSPECTIVE PRINCIPLES OF STATE VOCATIONAL SCHOOLS IN RIAU ISLANDS PROVINCE - Refri Yendri; M. Ikhsan; Ernik Yuliana (SEAN Institute, 2023)
From the results of the author's observations in the field, only 5.5% of 36 public vocational school principals in the Riau Archipelago do not have Saucy and NRKS certificates. There is 1 school principal in Anambas Islands Regency, and 1 person in Tanjungpinang City. While 31% of teachers who already have Saucy certification are available, but only available in Batam City (23%) and Tanjungpinang City (8%), the data suggests that the availability of prospective school principals is not evenly distributed, especially in areas far from the provincial capital. Teachers in areas far from the provincial capital are reluctant to participate in the selection of cute training because of the large costs of transportation and accommodation incurred when attending the cute training. Riau Archipelago Province. Knowing the supporting factors and inhibiting factors in the education and training program for prospective heads of State Vocational High Schools in the Riau Archipelago Province. The theory used in this study is that according to Dunn (2003: 610) policy evaluation is a policy that determines a better direction than the previous one with the following characteristics: 1. Effectiveness, 2. Efficiency 3. Adequacy. 4. Alignment 5. Responsiveness 6. Accuracy